1994
DOI: 10.1139/b94-226
|View full text |Cite
|
Sign up to set email alerts
|

La phénologie des arbres caducifoliés en forêt guyanaise (5° de latitude nord) : illustration d'un déterminisme à composantes endogène et exogène

Abstract: La phbnologie des arbres caducifoliCs en for& guyanaise (So de latitude nord) : illustration d'un dbterminisme h composantes endogkne et exogkne DENIS LOUBRY I Laboratoire d'e'cologie vdgdtale, Institut franqais de la recherche scientifique pour le de'veloppement en coopiration (ORSTOM), B. P. 165, 97323 Cayenne Cddex, Gicyane franqaise Recu le 15 dCcembre 1993 LOUBRY, D. 1994. La phCnologie des arbres caducifoliCs en forCt guyanaise (5" de latitude nord) : illustration d'un dCterminisme & composantes endogkne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 19 publications
1
20
0
4
Order By: Relevance
“…As a result, total canopy [CO 2 ] gradients during the wet season were about 40 mol mol )1 lower than those during the dry season. Since high decay factors have been reported for tropical forests (turnover rates 1.2-3.2 year )1 ; Whitmore 1990; Wieder and Wright 1995), and maximum litterfall in French Guiana forests generally occurs during July and August (Loubry 1994), lower soil respiration rates during the wet season were unexpected and counterintuitive. However, Wofsy et al (1988) attributed lower soil CO 2 efflux from an Amazonian forest soil during the wet season to a lower solar flux, which could reduce carbon allocation of plants to roots.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As a result, total canopy [CO 2 ] gradients during the wet season were about 40 mol mol )1 lower than those during the dry season. Since high decay factors have been reported for tropical forests (turnover rates 1.2-3.2 year )1 ; Whitmore 1990; Wieder and Wright 1995), and maximum litterfall in French Guiana forests generally occurs during July and August (Loubry 1994), lower soil respiration rates during the wet season were unexpected and counterintuitive. However, Wofsy et al (1988) attributed lower soil CO 2 efflux from an Amazonian forest soil during the wet season to a lower solar flux, which could reduce carbon allocation of plants to roots.…”
Section: Discussionmentioning
confidence: 98%
“…The canopy is stratified in three layers: an upper canopy formed by trees 25-35 m tall, a middle canopy at about 15-20 m, and an understory regeneration with saplings < 2 m tall. Three angiosperm families (out of 73 total) make up 60% of the rainforest in French Guiana, i.e., the Lecythidaceae (genera Eschweilera and Lecytis), the Caesalpiniaceae (genera Eperua and Dycorinia) and the Chrysobalanaceae (genera Licania and Parinari ;Favrichon 1994;Loubry 1994). The soil is a well-drained Oxisol on Precambrian bedrock.…”
Section: Sitementioning
confidence: 99%
“…We therefore suggest that the measurement of π tlp is informative of the responses of plant water use, and hence potentially growth and whole‐plant performance, during dry seasons (Mart, Veneklaas, & Bramley, ). Some of the trees shed their leaves, in species already known to be semi‐deciduous (Loubry, ). However, at our study site, deciduousness was not directly related to leaf drought tolerance as indicated by π tlp , in contrast with drier tropical forests (Sobrado, ; Xu, Medvigy, Powers, Becknell, & Guan, ), suggesting these adaptive strategies may respond to different constraints in rainforests as found elsewhere (Wright & van Schaik, ; Wu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we only had a clear view of the northerly forested landscape located near populated areas along the coast for which there are both litterfall records (Sabatier and Puig 1986) and quantitative observations on growth (Loubry 1994). Field data are extremely limited for the other forested landscapes, which are still difficult to access.…”
Section: Discussionmentioning
confidence: 99%